ANALYSIS OF CAI UTILIZATION AND TEACHERS' ATTITUDES ON BASIC SCIENCE STUDENTS’ ACHIEVEMENT IN OSUN STATE, NIGERIA - Bakare, Olusegun Ojo (Indonesian Journal of Elementary Teachers Education, 2024)
ABSTRACTBasic Science teachers in Nigerian schools are statistically few which might influence the way the subject is being taught.  Teachers have deployed different techniques or methods to teach Basic Science yet, students’ performance in the subject appeared low. This study examined influence of Basic Science teacher use of Computer Aided Instruction (CAI) on junior secondary school students’ academic performance in Osun State. Four research objectives guided the study. It adopted regression research design. All Basic Science teachers and students constituted population for the study. A sample size of 26 teachers and 307 junior secondary school students were selected using multistage sampling technique. Two instruments validated with reliability coefficient of 0.67 and 0.74 obtained using the split half method were used. Multiple regression analysis was used to test the hypotheses at 0.05 significant level. Findings of this study revealed that teachers’ characteristics do not statistically significant (F(8,17)=1.227, p= 0.342) predict the teacher’s use of CAI in teaching Basic Science in Osun State schools. It also found no significant variance in the intention to use CAI that predicted teacher characteristics (F(8, 17) = 1.227, p > .001, R² = 0.366). It further showed no teacher characteristics showing statistically significant influence on intention to use CAI in teaching Basic Science. It however found a statistically significant relationship (F(1, 305) = 10.269, p = 0.001) between teachers' intention to use CAI and junior secondary students' academic performance in Basic Science. It concluded that the teacher’s intention to use CAI significantly influence Basic Science students’ performance.Keywords: educational technology; Computer aided instruction; Teacher’s intention to use; Student’s Achievement; academic performance; Basic Science